Higher Education as a Determinant of Sustainable Economic Development of Ukraine: Financial Aspects - Nataliya Konstantyuk (Barometr Regionalny, 2016)
Higher education is of the foremost impact on the personality as the carrier of the knowledge-based capital. That is why the creation of knowledge-based capital is possible through the investment in higher education, the results of which are scientific investigations and innovations, which in total are in the heart of knowledge economy and the promoter of long term growth of the country. This thesis is confirmed by the expenditures for higher education, the most developed countries of the world spend a lot of financial resources for higher education and their expenditure for education can be treated as the strategic investments in nation economy of their country. It shows the relationship between the cost of education and the size of their GDP. Also the actual problems of financial support of higher education in Ukraine are examined, which hinder the development of education and the economy at all. There are recommendations for solving financial problems of higher education in Ukraine.